Factors influencing the construction cost of Industrialised Building System (IBS) projects - Ahmad Bari, Nor Azmi; Mohd Yusuff, Rosnah; Ismail, Napsiah; Jaapar, Aini; Ahmad, Rizan (Elsevier, 2012)
This paper presents the results of a survey of factors influencing the construction costs of Industrialised Building System (IBS) projects in Malaysia. The aim of the study was to evaluate and rank a range of factors that Malaysian IBS stakeholders regard as important, with the key identified factors being those associated with the main project characteristics, contract procedures and procurement methods, contractors’ and consultants’ attributes and design parameters besides external market conditions. Remarkably, factors grouped under the consultants and design parameters, external factors and government/authority requirements indicate low RII index while project/IBS characteristics, contractor attributes, external market conditions denote high RII index.